(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article raises questions about masks, their use and construction, based on a conversation with two friend s who studied together in the 1990s and then took different paths, but remained united by a common affection: masks and their facets. To tell you a little about this journey, we’ve drawn up a dialogue that shows a little of Patricia dos Santos’ history and the masks she came across along the way. Thus, through an interview, we unveil the possibilities of working with masks, of a sensitive look at the other and at oneself, revealing what is most human and poetic in everyday and theatrical masks.